Home-based rehabilitation programs on postural balance, walking, and quality of life in patients with stroke: A single-blind, randomized controlled trial. Issue 35 (3rd September 2021) - Lim, Jae-Heon; Lee, Hye-Sun; Song, Chiang-Soon
Abstract: Background: The most challenging aspect of rehabilitation is the high costs of in-patient rehabilitation programs and poor continuity of care while patients are transferred to home. In this regard, numerous home-based rehabilitation programs have been developed. The purpose of this study was to investigate the effects of home-based rehabilitative programs on postural balance, walking, and quality of life in individuals with chronic hemiparetic stroke. Design: A CONSORT-compliant randomized controlled trial. Methods: Seventeen community-dwelling people diagnosed with a first stroke participated in this study. They randomly divided the home-based rehabilitative program (HBP) group (n = 9) and control group (n = 8). The HBP group received coordination exercises at home and the control group received clinic-based exercises. This study measured postural balance, walking, and quality of life using four outcome measures: 10-meter walk test, figure of 8 walk test, four-square step test, and 36 item short-form survey. Results: After analysis, it was found that the HBP improved postural balance, comfortable speed, and fast speed walking, and straight and curved walking for chronic stroke. Second, clinic-based rehabilitation services improved postural balance, comfortable speed, and fast speed walking abilities in patients with chronic stroke. Conclusion: The results of this study suggest that the HBP group received positive benefits with regard to the postural balance and walking abilities of chronic hemiparetic stroke patients compared to the clinical setting exercise program.